Indonesian Language Proficiency Based on Gender of Junior High School Students in Lampung Province - Ardian, Dina; Samhati, Siti; Sumarti,; Rusminto, Nurlaksana Eko; Suyanto, Edi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
Indonesian language proficiency among junior high school students is an essential component of academic development and effective communication; however, differences based on gender during early adolescence remain underexplored. This study aims to describe Indonesian language proficiency levels of junior high school students in Lampung Province based on gender using data from the Indonesian Language Proficiency Test (UKBI). A quantitative descriptive research design was employed, utilizing secondary data from 8,204 UKBI participants, consisting of 3,192 male students (38.91%) and 5,012 female students (61.09%). Language proficiency was measured through three UKBI sections: listening, responding to grammatical rules, and reading comprehension, with the final score obtained from the average of these sections. Data were analyzed using descriptive statistical techniques, including mean scores and standard deviation, to examine proficiency levels and score distributions by gender. The findings reveal that the overall Indonesian language proficiency of junior high school students in Lampung Province is at a moderate level. Female students consistently achieved higher average scores than male students across all sections. Reading comprehension emerged as the strongest skill area, while listening showed the lowest performance for both genders. The relatively low standard deviation values indicate that students’ scores tend to cluster around the mean. In conclusion, Indonesian language proficiency differs by gender, with female students demonstrating superior performance in listening, grammatical sensitivity, and reading comprehension. These results highlight the need for gender-responsive instructional strategies, particularly to strengthen listening and grammatical competencies among male students.